Eco-Social Welfare and Green Transformation: Policy Integration for Just Transition and Social Sustainability - Durmus Senyapar, Hafize Nurgul (Technium Sustainability, 2026)
Global green transformation constitutes an ecological and technological transition, as well as a profound process of social restructuring that directly reshapes welfare systems, labor markets, and distributive justice. Despite this multidimensional character, dominant policy debates continue to privilege environmental performance and economic efficiency, thereby marginalizing the social foundations of sustainability. This qualitative exploratory study examines how eco-social welfare principles are articulated and operationalized within green transformation policies aligned with the Sustainable Development Goals (SDGs). Using inductive document-based thematic analysis, the study analyzes sustainability through an SDG-centered social justice lens, with particular emphasis on SDG 1 (No Poverty), SDG 7 (Affordable and Clean Energy), SDG 10 (Reduced Inequalities), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). The findings identify three interrelated eco-social domains shaping just transition dynamics: welfare adaptation to ecological risks and climate-induced vulnerability; inclusive governance and participatory justice; and capacity building and communication as foundations of community-based resilience. The results demonstrate that green transformation lacks democratic legitimacy and long-term social viability when social justice remains confined to normative commitments rather than being institutionally embedded in sustainability governance. By comparatively linking welfare adaptation, governance arrangements, and socio-communicative capacity across global policy discourses, the study contributes an analytically integrated perspective to the literature on just transition and eco-social policy, and advances the argument that SDG coherence cannot be achieved through technocratic green growth alone, but requires the systematic integration of social protection, participatory governance, and institutional trust into the core of environmental policy design.